The fundamental role of social validity in behavioral consultation in school settings. Issue 6 (8th December 2022) - Falletta‐Cowden, Neal; Lewon, Matthew
Abstract: Social validity refers to the extent to which applied behavior analytic (ABA) treatment goals, methods, and/or outcomes are acceptable and meaningful to stakeholders. The aim of this conceptual paper is to suggest how social validity may be promoted during behavioral consultation in school systems and how the assessment of various aspects of social validity contributes to this throughout the consultation process. Literature pertaining to the concept of social validity, rapport‐building, collaboration with stakeholders in behavioral school consultation, and the assessment of social validity are reviewed and synthesized. Social validity may be promoted in several domains: communication with consultees, collaborative selection of treatment methods and student objectives, consultee training, and measurement of outcomes meaningful to stakeholders. Social validity assessment can occur in all of these domains and is ideally a continuous process that informs all phases of consultation. There is a particular need for direct measurement of the social significance of behavioral consultation services. Social validity is integral to all aspects of the behavioral school consultation process, and it may be facilitated by incorporating valid social validity assessments into every stage of the consultation process. Practitioner points: Social validity is integral to all aspects of the behavioral school consultation process, and it may be facilitated by incorporating valid social validity assessments into every stage of the consultation process. Social validity in schools may be promoted in several domains: communication with consultees, collaborative selection of treatment methods and student objectives, consultee training, and measurement of outcomes meaningful to stakeholders. There is a need for tools that allow for the direct measurement of social validity on a continuous basis.